2018
DOI: 10.1175/jcli-d-18-0102.1
|View full text |Cite
|
Sign up to set email alerts
|

Later Wet Seasons with More Intense Rainfall over Africa under Future Climate Change

Abstract: Later wet seasons with more intense rainfall over Africa under future climate change Article Published Version Dunning, C., Black, E. and Allan, R. (2018) Later wet seasons with more intense rainfall over Africa under future climate change. Journal of Climate, 31. pp. 97199738. ISSN 0894 8755ABSTRACT Changes in the seasonality of precipitation over Africa have high potential for detrimental socioeconomic impacts due to high societal dependence upon seasonal rainfall. Here, for the first time we conduct a conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
178
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(221 citation statements)
references
References 86 publications
(171 reference statements)
25
178
0
Order By: Relevance
“…These results are consistent with Dunning et al (2018) who found that CMIP5 models over the equatorial region projected early-onset and cessation. Onset over equatorial East Africa is linked to the 700 mb zonal winds, the Madden Julian Oscillation, and sea surface temperature in the western Indian Ocean (Camberlin and Okoola 2003, Pohl and Camberlin 2006, Zaitchik 2017, Wainwright et al 2019.…”
Section: Projected Changes In Onset and Cessation 411 March To Maysupporting
confidence: 92%
See 2 more Smart Citations
“…These results are consistent with Dunning et al (2018) who found that CMIP5 models over the equatorial region projected early-onset and cessation. Onset over equatorial East Africa is linked to the 700 mb zonal winds, the Madden Julian Oscillation, and sea surface temperature in the western Indian Ocean (Camberlin and Okoola 2003, Pohl and Camberlin 2006, Zaitchik 2017, Wainwright et al 2019.…”
Section: Projected Changes In Onset and Cessation 411 March To Maysupporting
confidence: 92%
“…Additional delays of up to 4 d are projected in the mean cessation date under 2°C GWL compared to 1.5°C GWL ( figure 3(h)). During this season, under the 2°C GWL, the region is projected to have a season that starts and ends later consistent with findings from Dunning et al (2018).…”
Section: June To Septembersupporting
confidence: 73%
See 1 more Smart Citation
“…For example, the peak of the Sahel droughts of 1970 to 1985, precipitation decreased by 30% [65,66], suggesting that such a magnitude of change is possible again at some point in the future. Moreover, a number of climate change projection scenarios suggest a decrease in precipitation over Northern Africa and the Western parts of Africa [67], while the Eastern and Southern Africa are highly likely to experience increase precipitation by the end of the 21st century [68,69].…”
Section: Comparison Of Iws Irwr Paws and Wsimentioning
confidence: 99%
“…In addition, climate change seems to influence rainfall characteristics in the Sahel zone, such as false starts and early cessation of rainy seasons or increased frequency of intense daily rainfall [27,28]. Ref [29] also show an increasing precipitation intensity with a higher average precipitation per rainy day, a 5-10 days later start and end of the rainy season, but only a marginal change in the overall duration of the wet season.…”
Section: Study Areamentioning
confidence: 99%